The Effectiveness of Galactagogue Content on Breast Milk Production: A Scoping Review - karo, deliana br; Mufdlilah, Mufdlilah (Universitas Aisyah Pringsewu, 2023)
Providing counseling to breastfeeding mothers and giving extras through the use of galactagogues to support the secretion process in breast milk production is one of the measures taken to boost breast milk production. This study aimed to investigate and evaluate previously published research on the effects of galactagogues on breast milk production. Inclusion criteria in this review included Indonesian or English language studies published in the last five years and focused on the efficacy of galactagogues on breast milk production. The structure of this scoping review is based on the PRISMA-ScR Checklist, as outlined by Arksey and O'Malley. Literature searches used three databases, namely Wiley Online Library, PubMed, and Science Direct—critical appraisal using the Joana Briggs Institute (JBI) Appraisal Tool. There were 343 relevant articles, and 10 were selected according to the researcher's criteria. The review results discuss that galactagogue content can affect mothers' milk from the duration and frequency of mothers consuming galactagogue content during breastfeeding. It was concluded that galactagogue content affects increased breast milk production, reinforced by banana flowers, Coleus amboinicus lour, and local foods and plants containing galactagogues. In addition, how long galactagogues are used and their consumption frequency affect breastmilk production and proper nutrition in meeting additional nutritional needs for breastfeeding women.